Provision of supplementary foods and diet against weight gain in pregnant women with chronic energy deficiency - Erma Retnaningtyas; Della Dapiruru; Reno Palupi Yonni Siwi (Science Midwifery, 2023)
Pregnant women are vulnerable to CED nutritional problems. One way to cope is by providing additional food. This study analyzed the provision of supplementary food and dietary patterns on weight gain for pregnant women with CED at the Balantak Selatan Health Center, Banggai Regency. Research Cross sectional correlational. Population of 35 pregnant women. Sample of 32 responden with purposive sampling. Data collection with questionnaires, weight scales, measuring upper arm circumference. The results of the study of 32 responden Most of the 23 (71.9%) responden consumed additional food, most of the 23 (71.9%) responden ate regularly and the majority of 23 (71.9%) responden had weight gain body. Analysis test using Chi Square significance 0.000 < α = 0.05. There is a relationship between supplementary feeding and dietary patterns on weight gain for pregnant women with CED. Provision of additional food and regular eating patterns in pregnant women can prevent CED.